Sorption of norfloxacin, sulfamerazine and oxytetracycline by KOH-modified biochar under single and ternary systems. (September 2018) - Luo, Jiwei; Li, Xue; Ge, Chengjun; Müller, Karin; Yu, Huamei; Huang, Peng; Li, Jiatong; Tsang, Daniel C.W.; Bolan, Nanthi S.; Rinklebe, Jörg; Wang, Hailong
Graphical abstract: Highlights: KOH modification enhanced the sorption capacity of biochar for antibiotics. Sorption of norfloxacin and oxytetracycline was enhanced in ternary system. pH did not significantly influence sorption on KOH-modified biochar. π-π EDA and electrostatic interactions were the major sorption mechanisms. Abstract: Pollution of water by single antibiotics has been investigated in depth. However, in reality, a wide range of different contaminants is often mixed in the aquatic environment (contaminant cocktail). Here, single and competitive sorption dynamics of ionizable norfloxacin (NOR), sulfamerazine (SMR) and oxytetracycline (OTC) by both pristine and modified biochars were investigated. Sorption kinetics of the three antibiotics was faster in ternary-solute than single-solute system. Sorption efficiency was enhanced in the competitive system for NOR by the pristine biochar, and for OTC by both the pristine biochar and the modified biochar, while SMR sorption by the pristine biochar and the KOH-modified biochar was inhibited. Sorption was governed by electrostatic interactions, π-π EDA and H-bonds for antibiotics sorption by biochar. SMR and OTC sorption by biochar was influenced by cation bridging and surface complexation, respectively. This research finding will guide the development of treatment procedures for water polluted by multiple antibiotics.